Variability in Phytophthora nicotianae var. nicotianae causing leaf blight and fruit rot on sweet pepper (Capsicum annuum) in North-western Himalayas - P.N. SHARMA, JAYA CHAUDHARY*, D.K. BANYAL and (Indian Phytopathology, 2015)
The studies were undertaken on cultural, pathogenic and molecular diversity in Phytophthora nicotianae var. nicotianae associated with leaf blight and fruit rot of sweet pepper (Capsicum annuum L. var. grossum Sendt.) in Himachal Pradesh. Twenty-five isolates of P. nicotianae var. nicotianae collected from diverse sweet pepper-growing areas of Himachal Pradesh were categorized into 7 morpho-cultural groups based on colony characteristics like type of growth, colony colour, shape, colony margins and zonation. Pathogenic variability determined on an indigenous differential set comprising 10 genotypes, grouped the test isolates into 10 pathogroups without any congruence with the morpho-cultural groups. Genetic diversity analysis using Inter-Simple Sequence Repeat (ISSR) primers and UPGMA cluster analysis distinguished 25 isolates into two major clusters (Cluster I and Cluster II) with a similarity coefficient 88 %. Cluster I comprised 19 isolates and cluster II contained 6 isolates. Further, Cluster I and Cluster II were distinctly subdivided into 6 and 2 subgroups, respectively. Pathogenic and ISSR data clustered majority of isolates according to their geographical locations. High variability was observed among P. nicotianae var. nicotianae populations in the North-western Himalayas.